A listening classroom: The importance of decolonizing Christian education from within - Boom, Edith H. van der (International journal of Christianity & education, 2026)
Considering the pedagogical context set by Christian schools across Canada, this paper argues that Christian educators who identify as settlers need not only to continue to learn more about Indigenous peoples and their history but also begin the task of decolonizing their classrooms by creating space to listen to the voices of those who have been traditionally marginalized within Christian schools. This paper suggests the practice of critical reflection for Christian educators to uncover unconscious assumptions, biases, and other forms of injustice, thereby laying the groundwork for decolonization within Christian schools.